Computer Aided Systems Theory - EUROCAST 2015: 15th International Conference, Las Palmas de Gran Canaria, Spain, February 8-13, 2015, Revised Selected Papers - Moreno-Díaz, Roberto; Pichler, Franz; Quesada-Arencibia, Alexis (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2015)
This volume constitutes the papers presented at the 15thInternational Conference on Computer Aided Systems Theory, EUROCAST 2015, heldin February 2015 in Las Palmas de Gran Canaria, Spain.The total of 107 papers presented were carefully reviewedand selected for inclusion in the book. The contributions are organized intopical sections on Systems Theory and Applications; Modelling BiologicalSystems; Intelligent Information Processing; Theory and Applications ofMetaheuristic Algorithms; Computer Methods, Virtual Reality and ImageProcessing for Clinical and Academic Medicine; Signals and Systems inElectronics; Model-Based System Design, Verification, and Simulation; DigitalSignal Processing Methods and Applications; Modelling and Control of Robots;Mobile Platforms, Autonomous and Computing Traffic Systems; Cloud and OtherComputing Systems; and Marine Sensors and Manipulators.